Mathematics Teacher Competencies and Self-Efficacy in Implementing National Curriculum - Ramadian Radite; Heri Retnawati (Universitas Syiah Kuala, 2023)
The new Indonesia National Curriculum, the Merdeka Curriculum, was officially implemented in the 2022/2023 academic year. There are differences between public and private schools regarding facilities and teachers' employment status. Most teachers in public schools are Civil Servants (CST), while most private teachers are non-CST. This research analyzes the mathematics teachers' competence and self-efficacy of CST and non-CST in implementing the Merdeka Curriculum. This research used mixed methods of survey correlational and expos facto. The number of teacher respondents attained by purposive sampling was 34 CST and 54 non-CST. Teachers' competence data were collected using multiple-choice tests on professional and pedagogical competence. Self-efficacy data were collected using a questionnaire adapted from Bandura, while factors causing teachers' self-efficacy were collected using interviews. The research finding shows that in implementing the Merdeka Curriculum, (1) teachers' competence from both teachers' group was low, whereas self-efficacy were moderate, (2) there is no difference in competence between CST and non-CST, but there are differences in self-efficacy, and (3) factors that affect the differences in the self-efficacy are beliefs towards the success of implementing Merdeka Curriculum, support from the headmaster and the government, salary eligibility, and difficulties aspects.